The Relative Efficacy of Chemically Diverse Small-Molecule Enzyme-Inhibitors Against Anticoagulant Activities of African Spitting Cobra (Naja Species) Venoms - Chowdhury, Abhinandan; Lewin, Matthew R.; Zdenek, Christina N.; Carter, Rebecca; Fry, Bryan G. (Frontiers in Immunology, 2021)
African spitting cobras are unique among cobras for their potent anticoagulant venom activity arising from strong inhibition of Factor Xa. This anticoagulant effect is exerted by venom phospholipase A2 (Group I PLA2) toxins whose activity contributes to the lethality of these species. This anticoagulant toxicity is particularly problematic as it is not neutralized by current antivenoms. Previous work demonstrated this trait for Naja mossambica, N. nigricincta, N. nigricollis, and N. pallida. The present work builds upon previous research by testing across the full taxonomical range of African spitting cobras, demonstrating that N. ashei, N. katiensis, and N. nubiae are also potently anticoagulant through the inhibition of Factor Xa, and therefore the amplification of potent anticoagulant activity occurred at the base of the African spitting cobra radiation. Previous work demonstrated that the enzyme-inhibitor varespladib was able to neutralize this toxic action for N. mossambica, N. nigricincta, N. nigricollis, and N. pallida venoms. The current work demonstrates that varespladib was also able to neutralize N. ashei, N. katiensis, and N. nubiae. Thus varespladib is shown to have broad utility across the full range of African spitting cobras. In addition, we examined the cross-reactivity of the metalloprotease inhibitor prinomastat, which had been previously intriguingly indicated as being capable of neutralizing viperid venom PLA2 (Group II PLA2). In this study prinomastat inhibited the FXa-inhibiting PLA2 toxins of all the African spitting cobras at the same concentration at which it has been shown to inhibit metalloproteases, and thus was comparably effective in its cross-reactivity. In addition we showed that the metalloprotease-inhibitor marimastat was also able to cross-neutralize PLA2 but less effectively than prinomastat. Due to logistical (cold-chain requirement) and efficacy (cross-reactivity across snake species) limitations of traditional antivenoms, particularly in developing countries where snakebite is most common, these small molecule inhibitors (SMIs) might hold great promise as initial, field-based, treatments for snakebite envenoming as well as addressing fundamental limitations of antivenom in the clinical setting where certain toxin effects are unneutralized.